2014
DOI: 10.1007/s12039-013-0542-3
|View full text |Cite
|
Sign up to set email alerts
|

Selective hydrogenation of maleic anhydride over Pd/Al2O3 catalysts prepared via colloid deposition

Abstract: Pd/Al 2 O 3 catalysts were prepared via colloid deposition and the performance of the catalysts was examined in the selective hydrogenation of maleic anhydride to succinic anhydride. When the reaction was carried on in a batch system with 1,4-dioxane as the solvent (353 K and 1.0 MPa), high conversion of maleic anhydride (>98%) and high selectivity (>99%) for succinic anhydride were observed after 5 h. The as-prepared Pd/Al 2 O 3 catalyst also showed excellent performance in solvent-free system and fixed-bed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 34 publications
(20 reference statements)
0
19
0
1
Order By: Relevance
“…Interestingly maleic anhydride, obtained nowadays from the oxidation of n-butane, can be catalytically opened and further hydrogenated to generate succinic acid, a further important C4-building block. 53 The related C4-monocarboxylic acid and C4-aldehyde, butyric acid, and butyraldehyde, can be produced on a large scale via hydroformylation (and further oxidation) of propylene using common ruthenium and cobalt hydrido carbonyls complexes as homogeneous catalysts. 54 However, some trends in the production of long chain carboxylic acids (e.g., C6-caproic-, C8-caprylic-, and C10-capric acid) point markedly toward mild fermentation processes based on renewable resources, leaving aside the more classical synthetic ways involving pure triglyceride chemistry.…”
Section: Residual Biomass and Wastementioning
confidence: 99%
“…Interestingly maleic anhydride, obtained nowadays from the oxidation of n-butane, can be catalytically opened and further hydrogenated to generate succinic acid, a further important C4-building block. 53 The related C4-monocarboxylic acid and C4-aldehyde, butyric acid, and butyraldehyde, can be produced on a large scale via hydroformylation (and further oxidation) of propylene using common ruthenium and cobalt hydrido carbonyls complexes as homogeneous catalysts. 54 However, some trends in the production of long chain carboxylic acids (e.g., C6-caproic-, C8-caprylic-, and C10-capric acid) point markedly toward mild fermentation processes based on renewable resources, leaving aside the more classical synthetic ways involving pure triglyceride chemistry.…”
Section: Residual Biomass and Wastementioning
confidence: 99%
“…It is usually obtained by hydrogenation of maleic anhydride (MAN), although the product of this reaction varies depending on the reaction conditions. Several researches have investigated various catalysts for this reaction, such as Ru/C, Ni/HY-Al 2 O 3 , Pd/C, Pd/SiO 2 , Ni/TiO 2 and Pd/Al 2 O 3 [3][4][5][6][7][8][9]. The reaction pathways of hydrogenation of maleic acid (MA) are shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Torres et al reported achieving 100% selectivity for succinic anhydride through the reaction catalyzed by a mesoporous Ni/TiO 2 catalyst at low temperature [8]. Yuan et al reported achieving MA conversion of 98% and succinic anhydride selectivity of 99% using Pd/Al 2 O 3 catalyst under 1.0 MPa of H 2 pressure and 1,4-dioxane as solvent [5]. Among the various catalysts, the Pd/Al 2 O 3 catalyst has an advantage for the chemical industry due to the high thermal stability and high dispersion of Pd [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…For a wider utilization of SA, development of the catalyzed chemical synthesis method with high efficiency is an important issue. Maleic anhydride (or maleic acid) was the oxidation product from n -butene or butadiene over metal cathodes in electronic reactions or precious metal-catalysts under various conditions. Traditionally, SA was produced by hydration and/or hydrogenation of fossil-derived maleic anhydride or maleic acid (MA). In 1960s, in the homogeneous catalytic system, reduction of MA by chromous sulfate in water gave SA in 86% yield .…”
Section: Introductionmentioning
confidence: 99%